2-(1,3-Diphenylpropen-1,3-diolato)-1,3,2-(5-formylbenzo)dioxaborol: A `whole-molecule disorder' crystal structure - Ng, S.W. (Chinese Journal Structural Chemistry, 2010)
The boron atom in C(22)E(15)BO(5) is O,O'-chelated by the anions in a tetrahedral geometry, with the planar five- and six-membered chelate rings being orthogonal to each other. The molecule lies on a two-fold rotation axis. The molecule is disordered with respect to another molecule in a 93:7 ratio; the treatment of the `whole-molecule disorder' by employing a large number of restraints is described. Crystal data: C(22)H(15)BO(5), monoclinic C2/c, a = 17.1804(5), b = 12.9409(4), c = 9.8842(3) angstrom, beta = 124.832(2), V = 1803.82(9) angstrom(3) at -173 K.